2018
DOI: 10.3390/su10072157
|View full text |Cite
|
Sign up to set email alerts
|

The Links between Environmental Innovation and Environmental Performance: Evidence for High- and Middle-Income Countries

Abstract: Abstract:Technology innovation plays an increasingly prominent role in addressing global environmental challenges. In particular, environmental technology innovation (environmental innovation) is the most powerful and realistic alternative to achieve environmental sustainability and sustainable development. A better understanding of how environmental innovation affects the environment and how the effect differs by country is needed. This study analyzes how

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
(48 reference statements)
1
12
0
Order By: Relevance
“…Moreover, patents negatively and significantly affects the CO 2 emissions at 1% significance level, implies that a unit increase in patents decreases by 23% to 33% CO 2 emissions in ASEAN countries. Our results are similar to Choi and Han [54] and Dinda [46].…”
Section: Panel Fmols and Dols Resultssupporting
confidence: 91%
“…Moreover, patents negatively and significantly affects the CO 2 emissions at 1% significance level, implies that a unit increase in patents decreases by 23% to 33% CO 2 emissions in ASEAN countries. Our results are similar to Choi and Han [54] and Dinda [46].…”
Section: Panel Fmols and Dols Resultssupporting
confidence: 91%
“…For brevity, we do not present the coefficients of control variables and confine our discussion using LNPATENT and LNINVENT (The results are qualitative similar using LNGRANT). In Panel A, the coefficients of PLEDGE_DUM and PLEDGE_RATIO are consistently negative and significant at the 1% level for the subsamples of low HHI5 in columns (1,2,5,6), while the same coefficients are not significant for the subsamples of high HHI5 in columns (3,4,7,8). Hence, the impact of SP on innovation is more pronounced for firms with controlling shareholders that are marginally more likely to lose ownership control in the case where the lender liquidates pledged shares.…”
Section: Micro-foundation Of Testable Hypothesismentioning
confidence: 89%
“…In addition, our study is also motivated by the fact that innovation plays an important role in sustainable development of a country (Choi and Han [8]; Krozer and Nentjes [9]; Silvestre and Tirca [10]). The world economy has grown rapidly over the past decades, while pollution and climate change problems have become more severe than ever before.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies found the mixed or negative impact of technological innovation on CO2 emissions. In a study of a panel data of 33 high-income and 36 middle-income countries, Choi and Han (2018) demonstrated that environmental innovations lessen CO2 and SO2 emissions in high-income countries whereas, it is not the fact for middle-income countries. Their investigation also revealed that trade increases SO2 and CO2 emissions in middleincome countries.…”
Section: Literature On Technology-co2 Emissionsmentioning
confidence: 99%
“…The investigations conducted by Ang (2009); Sohag et al (2015); Ameer and Munir (2016); Salahuddin et al (2016); Yan et al (2017); Kahouli (2018); Khan et al (2018); Mensah et al (2018); Miao et al (2018); Xu and Lin (2018) revealed that different proxies of technology have a positive effect on environmental quality. Some of the scholars discovered the mixed or negative impact of technology on environmental quality (Choi and Han, 2018;Park et al, 2018).…”
Section: Introductionmentioning
confidence: 99%